IMPLEMENTING OUTDOOR ACTIVITIES TO IMPROVE STUDENTS’ ABILITY IN WRITING FACTUAL DESCIPTION - Khairani, Mustika; Apriliaswati, Rahayu; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was set out in order to know how the implementing outdoor activities improve students’ ability in writing factual description to the year-10 students at class MIA 2 of SMAN 9 Pontianak in academic year 2017/2018. This research was conducted through Classroom Action Reseacrh (CAR) in three cycles. The subjects of this research were the tenth grade English teacher and 36 students of year-10 at class MIA 2. In collecting the data, the researcher used field note, observation checklist, and students’ writing test. The result showed that implementing outdoor activities improved students’ ability in writing factual description. Furthermore, Minds on of Five Sense Writing in outdoor activities improved students’ability of using noun phrase with adjectives, also the Action stage of Five Sense Writing in outdoor activities could improve students’ ability of using the simple present tense. Moreover, the students’ motivation was improved by implementing the the Action stage of Five Sense Writing in Outdoor Activities. The action of Five sense Writing improved the students’ enthusiasm as well as their activeness. Therefore, the writer positively recommends the teacher to implement outdoor activities as one of various techniques in teaching process, especially in teaching writing factual description.Key Words: Outdoor Activities, Factual Description, Writing.